Board Composition and Firm Performance: Panel-level Analysis of Firms in Emerging Market - Shrivastav, Shikha Mittal; Kalsie, Dr. Anjala (Journal of Contemporary Research in Management (JCRM), 2016)
The paper analyses the relationship between Board Composition (proportion of non-executive directors) and Firm Performance of 145 non-financial NSE listed companies in India for a period of five years. The firm performance measures include Tobinâ€™s Q, Return on Assets, Return on Capital employed and Return on Equity. Econometric analysis is performed using Pooled OLS and Random Effect Model. The research findings reveal that Board composition has a negative and significant impact on firm performance. The results are robust for both econometric models and various performance measures used. The paper concluded that the negative impact of Board composition on firm performance is due to the fact that non-executive directors lack information about the operations of the firm which reduces their ability to function effectively hence reduces firm performance. Â 